Catecholamine induces endothelial dysfunction via Angiotensin II and intermediate conductance calcium activated potassium channel - Fan, Xuehui; Yang, Guoqiang; Yang, Zhen; Uhlig, Stefanie; Sattler, Katherine; Bieback, Karen; Hamdani, Nazha; El-Battrawy, Ibrahim; Dürschmied, Daniel; Zhou, Xiao-Bo; Akın, Ibrahim (Biomedicine & pharmacotherapy, 2024)
Endothelial dysfunction contributes to the pathogenesis of Takotsubo syndrome (TTS). However, the exact mechanism underlying endothelial dysfunction in the setting of TTS has not been completely clarified. This study aims to investigate the roles of angiotensin II (Ang II) and intermediate-conductance Ca2+-activated K+ (SK4) channels in catecholamine-induced endothelial dysfunction. Human cardiac microvascular endothelial cells (HCMECs) were exposed to 100µM epinephrine (Epi), mimicking the setting of TTS. Epi treatment increased the ET-1 concentration and reduced NO levels in HCMECs. Importantly, the effects of Epi were found to be mitigated in the presence of Ang II receptor blockers. Furthermore, Ang II mimicked Epi effects on ET-1 and NO production. Additionally, Ang II inhibited tube formation and increased cell apoptosis. The effects of Ang II could be reversed by an SK4 activator NS309 and mimicked by an SK4 channel blocker TRAM-34. Ang II also inhibited the SK4 channel current (ISK4) without affecting its expression level. Ang II could depolarize the cell membrane potential. Ang II promoted ROS release and reduced protein kinase A (PKA) expression. A ROS blocker prevented Ang II effect on ISK4. The PKA activator Sp-8-Br-cAMPS increased SK4 channel currents. Epinephrine enhanced the activity of ACE by activating the α1 receptor/Gq/PKC signal pathway, thereby promoting the secretion of Ang II. The study suggested that high-level catecholamine can increase Ang II release from endothelial cells by α1 receptors/Gq/PKC signal pathway. Ang II can inhibit SK4 channel current by increasing ROS generation and reducing PKA expression, thereby contributing to endothelial dysfunction.
Gesehen am 18.02.2025